Pelaksanaan Pola Kemitraan Pada Usaha Ternak Ayam Broiler Di Peternakan Septa Agung Nugraha I Desa Loano Kecamatan Loano Kabupaten Purworejo - Uswatun Hasanah; Isna Windani; Istiko Agus Wicaksono (Universitas Muhammadiyah Purworejo, 2016)
This study aims to determine the partnership pattern in the broiler chicken farm carried out by the Septa Agung Nugraha I farm and determine the feasibility of its business. The research method used is a case study. The research location is in Loano village, Loano district, Purworejo district. The results showed that the partnership pattern in the broiler chicken farming carried out by the Septa Agung Nugraha I farm was a plasma core pattern in which PT Maju Pasti Jaya Saliman Yogyakarta acted as a core company and Septa Agung Nugraha I's farm as a plasma farmer. The core company provides livestock production facilities in the form of DOC, animal feed, OVK, while the plasma breeders provide pens, equipment and labor. The broiler chicken farm, a partnership pattern between PT MPJ Saliman Yogyakarta and Septa Agung Nugraha I farm, deserves to be damaged because the R / C ratio> 1, π / C ratio> prevailing bank interest, labor productivity> the prevailing wage rate, NR> value land rent per production period.